2017
DOI: 10.1177/2047487317711048
|View full text |Cite
|
Sign up to set email alerts
|

Association of objectively measured sedentary behaviour and physical activity with cardiovascular disease risk

Abstract: Background We evaluated the association of accelerometer-based sedentary behaviour and physical activity with the risk of cardiovascular disease. Design The design of this study used a population-based, cross-sectional sample. Methods A subsample of participants in the Health 2011 Study in Finland used the tri-axial accelerometer (≥4 days, >10 h/day, n = 1398). Sedentary behaviour (sitting, lying) and standing still in six-second epochs were recognised from raw acceleration data based on intensity and device o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
81
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 24 publications
3
81
1
4
Order By: Relevance
“…Recent research using device-measured physical activity and assessing a variety of cardiometabolic health indicators indicates that bouts of MVPA of any length (ie, time duration) contribute to the health benefits associated with the accumulated total volume of physical activity. [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Of 40 comparisons within 14 studies, 78% (31 comparisons) indicated that bouts <10 minutes long were as good or better than bouts ≥10 minutes. 1 An additional 10% (4 comparisons) reported that bouts <10 minutes long were associated with risk reduction but did not make a direct comparison with bouts ≥10 minutes.…”
Section: Schizophrenia Dmentioning
confidence: 99%
“…Recent research using device-measured physical activity and assessing a variety of cardiometabolic health indicators indicates that bouts of MVPA of any length (ie, time duration) contribute to the health benefits associated with the accumulated total volume of physical activity. [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Of 40 comparisons within 14 studies, 78% (31 comparisons) indicated that bouts <10 minutes long were as good or better than bouts ≥10 minutes. 1 An additional 10% (4 comparisons) reported that bouts <10 minutes long were associated with risk reduction but did not make a direct comparison with bouts ≥10 minutes.…”
Section: Schizophrenia Dmentioning
confidence: 99%
“…There is consensus amongst the scientific and clinical communities that exercise improves an individual's health and quality of life. Increasingly, exercise training is being promoted by physicians as a primary life-style prevention for several diseases, particularly those of the cardiovascular system (Xu et al 2010;Boyle et al 2012;Wu et al 2013;Aune et al 2015;Vasankari et al 2017). However, the recommendation of exercise training as a preventative or therapeutic strategy for testicular dysfunction is more problematic since data relating the impact of exercise training on testicular function are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity (PA) is de ned as an energy expenditure of > 1.5 metabolic equivalents (METs). (1,2) Sedentary behaviour (SB) refers to lying down or sitting with an energy expenditure of ≤ 1.5 METs, and it has been recently identi ed as a risk factor for cardiovascular diseases (CVDs) independent from PA. (3)(4)(5)(6) PA has also been associated with CVDs in several studies. (1,5) Physical inactivity is an independent risk factor for CVDs.…”
Section: Introductionmentioning
confidence: 99%